Dinamika Slang di Era Digital: Studi Sosiolinguistik Tentang Pengaruh Aplikasi Tiktok pada Generasi Alfa - Azizah Azizah; Istiqomatul Kholif; Veny Fitriana Rahman; Rico Rafly Maulana; Kusyairi Kusyairi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Slang is a language that is often used among the Alpha generation which shows various different uses of language. The rise of social media can affect various groups such as children, teenagers, especially for the Alpha generation. This happens because parents often divert their attention to social media when they are young. This phenomenon is a concern about the erosion of the use of good and correct Indonesian. However, each use of language has its own characteristics in each language. The purpose of this study is to describe the process of forming various slang languages ​​among the Alpha generation on various social media. In this study, researchers used sociolinguistic studies to understand the dynamics of the use of Indonesian in the era of globalization. The approach used uses qualitative research methods and literature studies. A qualitative approach is used to obtain data sources from various information that supports our research. The data we use is the influence of the Tiktok application which aims to understand the viral phenomenon on the Tiktok application such as behavior, actions, and motivation by describing it in the form of words and sentences.